Burden of Hospitalization Associated with Seasonal Influenza in Toronto, Canada, 2011–2016. (4th October 2017) - Kain, Taylor; Coleman, Brenda L; Hassan, Kazi; Green, Karen; Katz, Kevin; Powis, Jeff; Richardson, David; Plevneshi, Agron; Kwong, Jeffrey C; Chung, Hannah; Gubbay, Jonathan B; Mcgeer, Allison; et al.
Abstract: Background: As indications for testing for influenza broaden, influenza is increasingly being diagnosed in association with hospitalization in adults. We report data on the burden of illness associated with laboratory confirmed influenza requiring hospitalization (LCI-H) in Toronto, Canada from 2010–2011 to 2015–2016. Methods: TIBDN has performed population-based surveillance for LCI-H in adults (≥15years) in Toronto and Peel Region, Canada since 2005. All positive tests for influenza are reported, patients are approached for consent and data collected by chart review and patient/physician interview. Death within 30 days of hospitalization was considered associated with influenza. Population data were obtained from Statistics Canada, with data by underlying condition obtained from literature review and provincial health administrative data. Results: Over 6 seasons, 5, 591 LCI-H episodes were identified: 1, 094 (20%) H1N1, 2, 847 (51%) H3N2, 415 (7%) A(not typed), 1A(H3N2 and H1N1) and 1, 235 (22%) B. The median age of patients was 71.4 years, with 69.3% of patients over 65 years of age; 3, 015 (53.4%) were female, 2, 618 (46.8%) had been vaccinated against influenza, and 683 (12.2%) were admitted from nursing homes. Incidence by age, influenza subtype and season is shown in Figures 1 and 2. The average annual incidence in healthy adults was 5 per 100, 000, compared with 0.8 per 1, 000 in adults with COPD or diabetes, 1.7 per 1, 000 in adults with cardiac disease, and >2 per 1, 000 in those with underlying kidney disease or immunosuppression. Overall, 12.8% of patients had a significant non-respiratory complication (eg. myocarditis, stroke, C. difficile infection). 720 (12.9%) required ICU admission, and 414 (7.4%) required mechanical ventilation. The median hospital length of stay was 9.58 days (IQR 3-11). None of 226 cases aged <30 years died; the case fatality rate increased from 1.8% in those aged 30–39 to 14.5% in those aged 90+ (Figure 3). Conclusion: Despite vaccination programs, influenza is a very common cause of hospitalization and death in our adult population. While surveillance for LCI-H underestimates the overall burden of influenza, it may nonetheless help to appropriately prioritize preventive programs. Disclosures: J. Powis, Merck: Grant Investigator, Research grant. GSK: Grant Investigator, Research grant. Roche: Grant Investigator, Research grant. Synthetic Biologicals: Investigator, Research grant. A. Mcgeer, Hoffman La Roche: Investigator, Research grant. GSK: Investigator, Research grant. sanofi pasteur: Investigator, Research grant.